Lake Amenities, Environmental Degradation, and Great Lakes Regional Growth. (January 2015) - Stephens, Heather M.; Partridge, Mark D.
Regional migration and growth are increasingly associated with high-quality in situ natural amenities. However, most of the previous US research has focused on the natural amenities of the Mountain West or the South. The Great Lakes, with their abundant fresh water and natural amenities, would also appear well positioned to provide the foundation for this type of economic growth. Yet, while some parts of the western Great Lakes region are prime examples of amenity-led growth, other areas in the eastern Great Lakes may not have capitalized on their natural amenities, perhaps because of their strong industrial legacy. Using a unique county-level data set for the Great Lakes region (including Indiana, Illinois, Michigan, Minnesota, New York, Ohio, Pennsylvania, and Wisconsin), we test whether growth in the region is associated with proximity to lake amenities and whether there are offsetting industrial legacy or pollution effects. We also examine whether amenities have additional attraction value for those with high levels of human capital. Consistent with theory that suggests that natural amenities are normal or superior goods, we find that coastal areas in the region are positively associated with increases in shares of college graduates. However, we find little evidence that lake amenities contribute to broader household migration, especially after 2000. Based on these results, there may be opportunities to leverage Great Lake amenities to support economic growth in terms of attracting individuals with high levels of human capital who are most likely to make quality of life migration decisions.